Teaching animal habitat selection using wildlife tracking equipment. (1st October 2016) - Laskowski, Jessica; Gillespie, Caitlyn; Corral, Lucia; Oden, Amy; Fricke, Kent; Fontaine, Joseph J.
ABSTRACT: We present a hands-on outdoor activity coupled with classroom discussion to teach students about wildlife habitat selection, the process by which animals choose where to live. By selecting locations or habitats with many benefits (e.g., food, shelter, mates) and few costs (e.g., predators), animals improve their ability to survive and reproduce. Biologists track animal movement using radio telemetry technology to study habitat selection so they can better provide species with habitats that promote population growth. We present a curriculum in which students locate "animals" (transmitters) using radio telemetry equipment and apply math skills (use of fractions and percentages) to assess their "animal's" habitat selection by comparing the availability of habitat types with the proportion of "animals" they find in each habitat type.